Penegakan Hukum Di Wilayah Laut Pada Wilayah Perbatasan Negara - Bormasa, Adolof; Pasalbessy, John Dirk; Ubwarin, Erwin (PATTIMURA Legal Journal, 2022)
Introduction: In the regulation of law enforcement, especially law enforcement in the sea area at the state border, almost all laws and regulations have accommodated the authority of each institution in carrying out law enforcement in the state border area, therefore it must be carried out properly so that it can realize security in the state border area. Purposes of the Research: To analyze regulations related to law enforcement in the sea area in the border area of ​​the State Methods of the Research: The type of research used in this paper is in the form of normative juridical legal research, namely legal research regarding the regulation of authority and the implementation of the authority given by positive legal provisions factually in each particular legal event that occurs in the border area of ​​the State, the research approach used is statutory approach, the sources of legal materials used are secondary and tertiary sources of legal materials and the collection of legal materials in this study is normative juridical. Results Originality of the Research: The results of the study show that regulations related to law enforcement in the border areas of special states of the sea have overlapping arrangements. The government and local governments in the border areas in carrying out law enforcement in the state border areas in the sea area have not been maximal in law enforcement, partly because of the limited law enforcement infrastructure in the state border area with the area of ​​the state border which is not directly proportional to the number of law enforcement personnel who is in the field. Law enforcement in national border areas as regulated in laws and regulations is not effective because there is no integrated synchronization and coordination in carrying out law enforcement in the country's border areas